Initial Teacher Training and Border Areas. Teachers in Culturally Diverse Classrooms. Arica and Parinacota Region [Formación Inicial Docente y Espacios Fronterizos. Profesores en Aulas Culturalmente Diversas. Región de Arica y parinacota1 - Norambuena-Carrasco, C (Universidad Austral de Chile, 2019)
The objective of the article is to analyze the initial training of practicing teachers in a frontier region and culturally diverse educational space and, based on this, to determine whether the educational practices of teachers of primary education in public schools in the region of Arica and Parinacota can be considered intercultural. The work has a qualitative approach that started with the interview of key informants (practicing teachers). The results obtained from the qualitative processing of the interviews of practicing teachers shows the absence of the intercultural, theoretical and practical theme, during the initial training which translates into practices arising from the experience and personal initiative of each teacher, more than from a systematic work for their performance in contexts of cultural diversity. © 2020.